Evaluating occupational exposures of dental nurses: A retrospective study - Hongmei Yuan; Rui Shi; Wenwen Chen; Ying Ma; Zhiqing Liu; Fan Liu; Jingmei Yang (Frontiers Media S.A., 2022)
ObjectiveThe objective of this study was to investigate occupational blood-borne pathogen exposure among dental nurses and their attitudes toward infected patients, as well as the effectiveness of the training course, to provide a scientific basis for improving the quality of safety management in the dental hospital.Materials and methodsThe study was conducted using questionnaires administered from November 2019 to December 2019 in three hospitals in Sichuan Province, China. Frequencies for answers were calculated and presented as percentages.ResultsIn total, 257 valid questionnaires were returned. Most (61.9%) nurses stated that they were involved in occupational exposure. Among them, 154 had experienced sharp injuries, and the syringe needle was the most common instrument for injuries (45.8%). Twenty-two individuals had mucosal exposure, and the proportion of eye exposure was the highest (90.9%). Only associations between training and mucosal membrane exposure were found; however, the relevance was weak (r = 0.141). Of the participants, 86.4% felt morally responsible for taking care of patients with infectious diseases, and most (92.6%) said they would continue with this career.ConclusionOccupational exposure, particularly to sharp injuries, was common in medical care among dental nurses; however, vocational training had little effect on their incidence. As dental nurses still have positive attitudes toward patients with infectious diseases, more effective training should be conducted.